Bulk and Short‐Circuit Anion Diffusion in Epitaxial Fe2O3 Films Quantified Using Buried Isotopic Tracer Layers. Issue 9 (9th March 2021) - Kaspar, Tiffany C.; Taylor, Sandra D.; Yano, Kayla H.; Lach, Timothy G.; Zhou, Yadong; Zhu, Zihua; Kohnert, Aaron A.; Still, Evan K.; Hosemann, Peter; Spurgeon, Steven R.; Schreiber, Daniel K.
Abstract: Self‐diffusion is a fundamental physical process that, in solid materials, is intimately correlated with both microstructure and functional properties. Local transport behavior is critical to the performance of functional ionic materials for energy generation and storage, and drives fundamental oxidation, corrosion, and segregation phenomena in materials science, geosciences, and nuclear science. Here, an adaptable approach is presented to precisely characterize self‐diffusion in solids by isotopically enriching component elements at specific locations within an epitaxial film stack, and measuring their redistribution at high spatial resolution in 3D with atom probe tomography. Nanoscale anion diffusivity is quantified in a ‐Fe2 O3 thin films deposited by molecular beam epitaxy with a thin (10 nm) buried tracer layer highly enriched in 18 O. The isotopic sensitivity of the atom probe allows precise measurement of the initial sharp layer interfaces and subsequent redistribution of 18 O after annealing. Short‐circuit anion diffusion through 1D and 2D structural defects in Fe2 O3 is also directly visualized in 3D. This versatile approach to study precisely tailored thin film samples at high spatial and mass fidelity will facilitate a deeper understanding of atomic‐scale diffusion phenomena. Abstract : Oxygen transport is quantified in epitaxial Fe2 O3 thin films synthesized with well‐defined, buried 18 O isotopic tracer layers. Visualization of tracer redistribution by atom probe tomography reveals diffusion pathways and rates in the pristine lattice and along structural defects. This flexible approach provides novel insight into the fundamental mechanisms of atomic diffusion under external stimuli.